A numerical approach for solving problems in robotic arm movement. Issue 1 (1st January 2018) - Alsultan, Thaer; M. Ali, Hussein; Y. Hamid, Qussay
ABSTRACT: Mechanical robotic arm control problems are examined in the numerical solutions for the second order system with the R.Kutta algorithms. The dynamics of a robotic arm be able to designated by a set of combined non-linear equations in the formula of coriolis, centrifugal effects and gravitational torques. This investigation attempted to minimize the error of an industrial robotic arm, which improves production systems. Results of comparisons illustrate the effectiveness of the numerical integrating algorithm based on the actual joint velocities and positions with each instant of time between the exact and numerical solutions. The obtained tables of data help to analyze the variation in the velocity and position joints at different time. The numerical results obtained by R.kutta -techniques perfectly match with the exact velocities. Depending on the relative error calculated at the obtained tables of results to reach the required motion of the mechanical robot arm.